Three new species of Calliceratomyia Lane (Diptera: Ditomyiidae) from Neotropical Mexico - Huerta, Heron; Amorim, Dalton De Souza (Zootaxa, 2016)
Three new species of the ditomyiid genus Calliceratomyia Lane, so far known only from the type-species from southeastern Brazil, are described from Mexico. The new species—Calliceratomyia papaveroi sp. n., Calliceratomyia pantelhomyia sp. n. and Calliceratomyia zayolli sp. n.—are described based on adult males collected with Malaise traps in the States of Oaxaca, Chiapas and Hidalgo, Mexico. The descriptions are illustrated and the diagnosis of the genus is revised.